The PENERAPAN PENDEKATAN KEPEMIMPINAN SITUASIONAL DALAM MENGHADAPI TANTANGAN PEMBELAJARAN BERBASIS TEKNOLOGI ABAD 21 (STUDI KASUS DI SDN 67 PEKANBARU): Penerapan Pendekatan Kepemimpinan Situasional dalam menghadapi tantangan pembelajaran berbasis teknologi Abad 21 (Studi Kasus di SDN 67 Pekanbaru ) - Vovi Tridian Ulfah; Hartina Rastam; Hendri Marhadi; Mahmud Alpusari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT Education is a fundamental right of every citizen, guaranteed by the constitution, with the aim of educating the nation and creating a civil society. In Indonesia, education has adapted greatly to the developments and needs of the times. Faced with the challenges of changing times, a rapid and appropriate transition in education is needed to produce graduates who are able to adapt. School principals play a key role in improving the competence of teachers as the frontline implementers of new regulations on education. The ability of school principals to motivate, guide, and understand technological developments is important so that teachers have the enthusiasm and ability to design the latest learning methods, especially 21st-century technology-based learning. Thus, school principals are required to be able to adapt their leadership to the current situation. This research uses qualitative research with a case study approach. There are two main focuses: 1) How is the leadership of the principal at SDN 67 Pekanbaru from a situational leadership perspective? 2) How does the principal at SDN 67 Pekanbaru make decisions from a situational leadership perspective? 3) How does the principal prepare teachers to implement 21st-century technology-based learning from a situational leadership perspective? This research is expected to provide in-depth knowledge and insight into the leadership of the principal and the principal's ability to face the challenges of 21st-century technology-based learning at SDN 67 Pekanbaru from a situational leadership perspective.